Acknowledging and Addressing Microaggressions: A Virtual Experiential Learning Approach for Faculty - Jenna Essakow; April Edwell; Elisabeth Smith; Sneha Daya (Association of American Medical Colleges, 2024)
Introduction Although the ACGME and other accrediting organizations are increasingly emphasizing the importance of clinical learning environments that value diversity, equity, and inclusion, faculty development surrounding behavioral skills that promote inclusivity in the learning environment still needs cultivation. We designed a virtual longitudinal faculty development curriculum focused on direct observation, feedback, and practice of behavioral skills to acknowledge and address microaggressions in the learning environment. Methods We used Kern's six steps of curriculum development to create four voluntary virtual workshops offered twice throughout the academic year, with topics including: (1) recognizing and naming microaggressions, (2) apologizing when harm has been experienced, (3) setting expectations surrounding microaggressions, and (4) debriefing microaggressions. Participant learners included residency program directors, associate program directors, and other leaders across all medical and surgical departments from one institution. Results Thirty-one faculty from 10 departments participated in this yearlong curriculum. Pre- and postworkshop surveys analyzed participants' self-assessments of confidence and comfort in applying learned skills. Participants were more confident in openly naming bias, delivering expectations surrounding microaggressions, and debriefing microaggressions with learners. Participants also reported greater comfort in apologizing to learners when harm has occurred in public, in person, and electronically. Discussion To create an inclusive learning environment, faculty can increase their comfort and confidence with addressing bias and microaggressions through practice and feedback. Our curriculum demonstrates how experiential learning allows for continual practice to solidify a new skill.